2015
DOI: 10.1208/s12248-015-9781-1
|View full text |Cite
|
Sign up to set email alerts
|

Application of Absorption Modeling in Rational Design of Drug Product Under Quality-by-Design Paradigm

Abstract: Abstract. Physiologically based absorption models can be an important tool in understanding product performance and hence implementation of Quality by Design (QbD) in drug product development. In this report, we show several case studies to demonstrate the potential application of absorption modeling in rational design of drug product under the QbD paradigm. The examples include application of absorption modeling-(1) prior to first-in-human studies to guide development of a formulation with minimal sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 29 publications
0
34
0
1
Order By: Relevance
“…However, for compounds with a significant pH-dependent solubility or a high supersaturation propensity, measured equilibrium solubility at neutral pH may not adequately model dissolved drug concentration throughout the entire absorption window. In these cases, the use of biorelevant dissolution tools along with more sophisticated absorption modeling tools such as MiMBa®, GastroPlus®, STELLA®, or Simcyp® might be better suited [32][33][34][35][36]. The solid form from either undissolved or precipitated material should also be assessed as a change in polymorphic form can affect solubility and dissolution [37].…”
Section: Absorption Modeling To Facilitate Delivery and Formulation Amentioning
confidence: 99%
“…However, for compounds with a significant pH-dependent solubility or a high supersaturation propensity, measured equilibrium solubility at neutral pH may not adequately model dissolved drug concentration throughout the entire absorption window. In these cases, the use of biorelevant dissolution tools along with more sophisticated absorption modeling tools such as MiMBa®, GastroPlus®, STELLA®, or Simcyp® might be better suited [32][33][34][35][36]. The solid form from either undissolved or precipitated material should also be assessed as a change in polymorphic form can affect solubility and dissolution [37].…”
Section: Absorption Modeling To Facilitate Delivery and Formulation Amentioning
confidence: 99%
“…PBPK modeling provides a quantitative and mechanistic methodology that connects a drug’s Critical Quality Attributes (CQAs), which encompass a large variety of modeling parameters such as manufacturing criteria and drug-specific properties, to its in vivo behavior as characterized by its Quality Target Product Profile (QTPP). In recent years, studies hailing from academia as well as industry demonstrated how these models can be implemented within the Quality by Design paradigm [44,45] such that PBPK modeling developed intoa powerful and essential tool to increase mechanistic understanding and provide a holistic description of drug exposure in the body.…”
Section: Evolution Of Physiologically-based In Silico Predictionsmentioning
confidence: 99%
“…Kesisoglou and Mitra demonstrated how PBPK modeling could be implemented in the rational design of drug product under the Quality by Design (QbD) paradigm with the goal of linking the product critical quality attributes (CQAs) to the quality target product profile (QTPP) [44]. The first study evaluated the effects of gastric pH on absorption of a BCS Class II/IV compound relative to the QTPP, prior to first in human studies.…”
Section: Formulation Considerations For Special Populationsmentioning
confidence: 99%
See 2 more Smart Citations